Spontaneously formed gradient chemical compositional structures of niobium doped titanium dioxide nanoparticles enhance ultraviolet- and visible-light photocatalytic performance - Naoki Tarutani (Nature Portfolio, 2021)
Abstract Semiconductor photocatalysts showing excellent performance under irradiation of both ultraviolet (UV)- and visible (VIS)-light are highly demanded towards realization of sustainable energy systems. TiO2 is one of the most common photocatalysts and has been widely investigated as candidate showing UV/VIS responsive performance. In this study, we report synthesis of Nb doped TiO2 by environmentally benign mechanochemical reaction. Nb atoms were successfully incorporated into TiO2 lattice by applying mechanical energy. As synthesized Nb doped TiO2 were metastable phase and formed chemical compositional gradient structure of poorly Nb doped TiO2 core and highly Nb doped TiO2 surface after high temperature heat treatment. It was found that formed gradient chemical compositional heterojunctions effectively enhanced photocatalytic performance of Nb doped TiO2 under both of UV- and VIS-light irradiation, which is different trend compared with Nb doped TiO2 prepared through conventional methods. The approach shown here will be employed for versatile systems because of simple and environmentally benign process.